Corporate risk taking and sustainability: a case of listed firms from USA and Germany. Issue 1 (21st February 2019) - Younas, Zahid Irhsad; Zafar, Ameena
Abstract : Purpose: This study aims to analyze the impact of corporate risk taking on the sustainability of firms in USA and Germany. As risk taking is an expensive phenomenon, the firm may shift the resources from stakeholder well-being to profit maximization of shareholders. Ultimately, risk taking results in the reduction of firm's sustainability. Design/methodology/approach: To capture the impact of corporate risk taking, the corporate-governance variables, i.e. "independent board structure" and "board size, " were used as instrumental variables to control excessive corporate risk taking and restrict it at a healthy level. A sample of 3, 387 unbalanced panel observations from USA and Germany, for the period 2004-2015, were assessed. Findings: The results confirm that corporate risk taking has a negative and significant impact on the sustainability of firms. Research limitations/implications: Government and policymakers in USA and Germany may introduce regulations to curb excessive corporate risk taking for sustainable corporations and sustainable society. This research suggests that corporate risk taking is not in the best interest of stakeholders. Originality/value: Previous literature only finds the impact of sustainability on corporate risk taking and there is not a single study that examines the impact of corporate risk taking on the sustainability of a firm. Thus, this study contributes to existing literature on corporate risk taking and sustainability. The study further contributes by using the instrumental variable two stage least square.